Tumor Microbiome in Nasopharyngeal Carcinoma and Its Association With Prognosis - Zhong, Guihua; Wei, Wei; Liao, Wei; Wang, Rong; Peng, Yingpeng; Zhou, Yuling; Huang, Xiaotao; Xian, Shiping; Peng, Shunli; Zhang, Zhaoyuan; Feng, Shaoyan; Liu, Ye; et al. (Frontiers in Oncology, 2022)
Abstract Introduction: Previous studies have reported a close relationship between cancer and microbes, particularly gut and tumor microbiota; however, the presence of tumor microbiome in nasopharyngeal carcinoma (NPC) and its role in the prognosis of NPC are remain unclear. Thus, we applied 16S ribosome RNA gene sequencing of nasopharyngeal samples to assess microbiome profiles and utilized immunohistochemistry to detect tumor microbiome in NPC. Methods: We collected 64 samples including 50 patients with NPC and 14 patients with chronic nasopharyngitis and we applied 16S ribosome RNA gene sequencing of all samples to assess microbiome profiles and immunohistochemistry to detect tumor microbiome in NPC. Results: Patients in the control group harbored higher species diversity than those in the NPC group; however, the beta diversity was more distinct in the NPC group. In total, three genera with statistically significant differences between the two groups were identified. The area under the ROC curve (AUC) was calculated using relative abundance of these three significant genera, and a value of 0.842 was achieved. Furthermore, Turicibacter was confirmed as an independent prognostic factor for NPC patients, and the progression-free survival (PFS) was markedly prolonged in patients with a high relative abundance of Turicibacter than patients with a low relative abundance of this genus (cutoff: 0.0046, hazard ratio: 5.10, 95% confidence interval: 2.04–12.77, p = 0.004). Conclusions: The present study provided strong evidence of a correlation between tumor microbiome and NPC; the tumor microbiome probably may be considered a biomarker for early NPC diagnosis. Turicibacter served as a good prognostic indicator for NPC patients.